Permodelan Spasial pada Analisis Faktor yang Mempengaruhi Tingkat Pengangguran Terbuka Provinsi Bangka Belitung Tahun 2018 - Apriliansyah Mahmud; Ernawati Pasaribu (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
Unemployement is a multidimensional problem that have wide impact into progress and quality of one area. Based on that problem, it is necessary to have an analysis of factor that affected this phenomena. One economy phenomenon of one area can be influenced by neighborhood economy activity. The purpose of this study is to know factors that affected open unemployemnet rate also answer the problem of neighborhood effect by spatial model. Based on result, variables that having spatial effect are open unemployement rate, count of poor citizen, and also gross domestic product. Beside of that, it is also known that error spatial model is feasible to be a model because having smallest AIC score.